AIE Luminogens as Versatile Bioprobes - Gabr, Moustafa T.; Pigge, F. C. (Current Analytical Chemistry, 2021)
Background: Luminogens that feature aggregation induced emission (AIE) are typically non-emissive in solution but become highly luminescent upon aggregation in poor solvents or solid state. Discussion: Unlike conventional fluorophores that exhibit aggregation-caused quenching (ACQ), utilization of AIE luminogens as bioprobes has featured superior photostability, low background signal, large Stokes’ shifts, high sensitivity and turn-on luminescent response. Conclusion: The versatility of AIE-based luminogens as bioprobes has been demonstrated through various applications in cell organelle imaging, ion sensing and sensitive detection of biomacromolecules. Examples of AIE-based luminogens and their applications as luminescent sensors for biosensing and optical imaging are discussed herein.
Keywords: organelle imaging